Highly active antiretroviral therapy discontinuation time is associated with therapeutic failure among human immunodeficiency virus (HIV)-infected immigrant adults: A cohort study from a Peruvian referral hospital during the Venezuelan exodus - Rebolledo-Ponietsky, Kirbeliz (2023)
Objective: To evaluate the association between Highly Active Antiretroviral Therapy (HAART) discontinuation time and therapeutic failure (TF) in Venezuelan immigrants with HIV that restart HAART. Methods: We carried out a retrospective cohort study in a large hospital in Peru. We included Venezuelan immigrants who restarted HAART and were followed over at least 6 months. The primary outcome was TF. Secondary outcomes were immunologic (IF), virologic (VF) and clinical (CF) failures. The exposure variable was HAART discontinuation, categorised as no discontinuation, less than 6 months, and 6 months or more. We applied generalised linear models Poisson family with robust standard errors to calculate crude (cRR) and adjusted (aRR) relative risks by statistical and epidemiological criteria. Results: We included 294 patients, 97.2% were males, and the median age was 32 years. Out of all the patients, 32.7% discontinued HAART for less than 6 months, 15.0% discontinued for more than 6 months and the remaining 52.3% did not discontinue. The cumulative incidence of TF was 27.9%, 24.5% in VF, 6.0% in IF and 6.0% in CF. Compared with non-discontinued HAART patients, the discontinuation for less than 6 months (aRR = 1.98 [95% CI: 1.27–3.09]) and from 6 months to more (aRR = 3.17 [95% CI: 2.02–4.95]) increased the risk of TF. Likewise, treatment discontinuation of up to 6 months (aRR = 2.32 [95% CI: 1.40–3.84]) and from 6 months to more (aRR = 3.93 [95% CI: 2.39–6.45]) increased the risk of VF. Conclusions: HAART discontinuation increases the probability of TF and VF in Venezuelan immigrants.